The Role of Aesthetic Properties of Granitic Dimension Stones on Marketability: A Case Study of CIBI Nigeria Limited, Kaduna State - IDOWU, Kayode A.; JESSEY, Victory N.; SAMANI, Emmanuel B. (FUDMA Journal of Engineering and Technology, 2026)
This study investigates the disconnect between aesthetic quality and market positioning of locally sourced granite at CIBI Nigeria Limited, Kaduna State. The study was motivated by the growing need to understand how intrinsic stone qualities translate into commercial value in emerging markets. Through mixed-methods analysis involving visual/tactile assessment of ten granite samples and perspectives from management/sales personnel (n=10), findings reveal that CIBI’s products possess premium aesthetic attributes; diverse colours (Zaria Red, Champagne Gold), distinctive veining/speckling patterns, and consistently high lustre (mean score 5.0/5.0). These aesthetic strengths, however, are not fully reflected in the company’s commercial strategies. Despite 80% of personnel rating their granite as “very competitive” against imports, the company employs a cost-based rather than value-based pricing strategy, with aesthetics treated as secondary to logistical factors (transportation costs from quarry sites). Marketing relies heavily on traditional channels (brochures, sales teams; mean effectiveness 4.4-4.5/5.0) while digital platforms remain underutilised (website effectiveness 3.8/5.0). These findings point to a systemic misalignment between product quality and market communication that constrains the company’s commercial performance. The study recommends strategic adoption of value-based pricing and investment in digital marketing infrastructure to align external communication with proven product quality and capture premium market segments.